Laparoscopic and robotic specimen retrieval system (Modified Nadiad Bag): Validation and cost-effectiveness study model - Chaitanya Sharad Deshmukh; Arvind P Ganpule; Mohammad Rafiqul Islam; Ravindra B Sabnis; Mahesh R Desai (Journal of Minimal Access Surgery, 2019)
Aim: To construct and validate a cost-effective indigenously made retrieval system (Modified Nadiad bag) in minimal access urology. Method: The components of the modified Nadiad bag are a polyethylene roll, fishnet thread, and a 5 Fr ureteral catheter. The bag is indigenously made in our institute and used for organ retrieval after proper sterilization. The video recordings of entrapments and retrievals done over the past few months were reviewed. The procedures under review in which the bag was used were: Robot Assisted Radical Prostatectomy (50 cases), laparoscopic radical nephrectomy (50 cases), laparoscopic simple nephrectomy (50 cases) and laparoscopic adrenalectomy (18 cases). We also compared the retrieval time with experts and novices. Results: The retrieval times, the organ size (largest dimension) and specimen weight were records for each case. Multivariate analysis of the data was done and we extrapolated the retrieval time with organ size, specimen weight and expertise of the surgeon. There was no significant difference among expert surgeons and novice surgeons with regards to retrieval times (p value = 0.29), with regards to organ size (p value = 0.83) and with regards to specimen weight (p value = 0.99). Conclusion: Our design of retrieval system offers a cost-effective option which is easy to make, without the risk of tumor seeding and without the need for separate access sheath. It's a retrieval system which has proved its efficacy in laparoscopic as well as robotic procedures with no bearing on the expertise of the surgeon involved.